Academic and Community ICUs Participating in a Critical Care Randomized Trial: A Comparison of Patient Characteristics and Trial Metrics. (18th November 2022) - Tsang, Jennifer L. Y.; Binnie, Alexandra; Duan, Erick H.; Johnstone, Jennie; Heels-Ansdell, Diane; Reeve, Brenda; Trop, Sebastien; Hosek, Paul; Dionne, Joanna C.; Archambault, Patrick; Lysecki, Paul; Cirone, Robert; et al.
Abstract : OBJECTIVES: Clinical research in Canada is conducted primarily in "academic" hospitals, whereas most clinical care is provided in "community" hospitals. The objective of this nested observational study was to compare patient characteristics, outcomes, process-of-care variables, and trial metrics for patients enrolled in a large randomized controlled trial who were admitted to academic and community hospitals in Canada. DESIGN: We conducted a preplanned observational study nested within the Probiotics: Prevention of Severe Pneumonia and Endotracheal Colonization Trial (PROSPECT, a randomized controlled trial comparing probiotics to placebo in mechanically ventilated patients) Research Program. SETTING: ICUs. PATIENTS: Mechanically ventilated patients. MEASUREMENTS: We compared patient characteristics, interventions, outcomes, and trial metrics between patients enrolled in PROSPECT from academic and community hospitals. MAIN RESULTS: Participating centers included 34 (82.9%) academic and seven (17.1%) community hospitals, which enrolled 2, 203 (86.2%) and 352 (13.8%) patients, respectively. Compared with academic hospitals, patients enrolled in community hospitals were older (mean [sd ] 62.7 yr [14.9 yr] vs 59.5 yr [16.4 yr]; p = 0.044), had longer ICU stays (median [interquartile range IQR], 13 d [8–23 d] vs 11 d [7–8 d]; p = 0.012) and higher mortality (percentage, [95% CI] in the ICU, 30.4% [25.8–35.4%]vs 20.5% [18.9–11.3%]; p = 0.002) and hospital (40.6% [35.6–45.8%] vs 26.1% [24.3–27.9%]; p < 0.001). Trial metrics, including informed consent rate (85.9% vs 76.3%; p = 0.149), mean (sd ) monthly enrolment rate (2.1 [1.4] vs 1.1 [0.7]; p = 0.119), and protocol adherence (90.6% vs 91.6%; p = 0.207), were similar between community and academic ICUs. CONCLUSIONS: Community hospitals can conduct high-quality research, with similar trial metrics to academic hospitals. Patient characteristics differed between community and academic hospitals, highlighting the need for broader engagement of community hospitals in clinical research to ensure generalizability of study results.